(untitled) (Revista Científica Integrada, 2023)
Aim: To build a terminological subset of the International Classification for Nursing Practice (ICNP®) for institutionalized elderly people, based on Virginia Henderson’s Theory of Fundamental Human Needs (NHF). Methods: Methodological study, following the steps: mapping of the Nursing Diagnoses/Outcomes (ND/NO) with the pre-coordinated concepts of the ICNP® version 2017; construction of operational definitions of ND/RE concepts; validation by consensus of the ND/RE concepts and their respective operational definitions; construction and validation of Nursing Interventions (IE) for each validated ND/NO; structuring of the terminological subset. Results: 133 ND/RE and 1474 IE concepts were validated, most of which were classified in the Biological/Physiological Component, for the terminological subset for institutionalized elderly people. Conclusion: It is expected that the constructed terminological subsets can serve as an easily accessible reference for the nurse and favor comprehensive care for the elderly in Long Stay Institutions for the Elderly.